Pengaruh Model Project-Based Learning dan Penggunaan Simulator terhadap Hasil Belajar Mata Pelajaran Computer Numerical Control - Sholahuddin Al Ayubi; Khoirul Huda; Kriswanto Kriswanto (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study examines the effectiveness of implementing a Project-Based Learning model combined with a CNC simulator in improving student learning outcomes in Computer Numerical Control at SMK IPT Karangpanas. The research design used a one-group pretest-posttest. The study sample consisted of 43 11th-grade Machining Engineering students. Pre-test data were obtained from the final grades of semester 1 with an average of 80.7, while post-test data were obtained after the intervention in semester 2 with an average of 82.6. The Shapiro-Wilk normality test showed a significance value of 0.205 (>0.05), indicating a normally distributed data. Furthermore, an independent t-test yielded p=0.003 (<0.05), indicating a statistically significant increase in learning outcomes. These findings confirm that the integration of Project-Based Learning (PjBL) and CNC simulation media can improve students' conceptual understanding and technical skills. It is recommended that this model be implemented in technology-based vocational learning, utilizing simulation tools optimally, and conducting regular formative evaluations to maximize competency achievement.